Multipurpose legumes for smallholders in sub-Saharan Africa: Identification of promising ‘scale out’ options - Snapp, Sieglinde S.; Cox, Cindy M.; Peter, B.G. (Elsevier, 2019)
Legumes are often cited as essential components for sustainable agriculture development in Africa, yet investment in germplasm improvement and in understanding adoption of these important crops has been modest. In this review, we present promising legume options by farming system niche, thus providing an ecological as well as socio-economic lens for better policy decision making. We focus on multipurpose legumes with complementary growth habits that can be grown in conjunction for enhanced agriculture sustainability. We also show the region's spatially-explicit distribution of chickpea, common bean, cowpea, groundnut, and pigeonpea, and define the climate niche for expansion of these crops through Google Earth Engine. Multipurpose legumes provide ‘scale out’ opportunities for smallholder farmers in sub-Saharan Africa, but not without considerable investment.